A Qualitative Study of Nursing Management in Iran - Kalateh Sadati, Ahmad (J Environ Public Health, 2021)
BACKGROUND: Nursing managers have a critical role at the hospitals. The current study aims to investigate different experiences of nursing managers. METHOD: This is a qualitative study that investigates the experiences of 11 nursing managers in Shiraz, Iran. Semistructured interviews and thematic analysis were, respectively, applied for data collection and analysis. RESULTS: It could be found from the current investigation that nursing managers have a critical role at the hospitals, and their creativities have more impacts on procedures compared to organizational orders. There are four major challenges faced by nursing managers including nursing shortage, structural deficiencies, lack of authorities, and burnout. Although shortage is considered as the most important challenge, there are more emphasizes on the improvement of their controlling power in order to prevent their fatigue and burnout. CONCLUSION: This study showed that creativity of nursing managers is the most important factor of system management; also, shortage and deficiencies are recognized as the most significant challenges faced by them. According to the current study, the shortage of nursing staff is the central issue that has to be considered.